2003
DOI: 10.1016/s0042-6822(03)00236-8
|View full text |Cite
|
Sign up to set email alerts
|

The leader peptide of MMTV Env precursor localizes to the nucleoli in MMTV-derived T cell lymphomas and interacts with nucleolar protein B23

Abstract: We have previously described two nucleolar proteins, named p14 and p21, in MMTV-induced T cell lymphomas. These proteins were identified by a monoclonal antibody (M-66) generated from a nontumorigenic, immunogenic variant of S49 T cell lymphoma. While p14 was common to several MMTV-derived T cell lymphomas, p21 was found only in highly tumorigenic variants of S49 cells. Here we report that p14 is the leader peptide of the MMTV env precursor. The epitope recognized by M-66 contains a putative nuclear localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 37 publications
8
27
0
Order By: Relevance
“…Although a variety of viral proteins are translocated into the nucleolus following viral infection (33), we were the first to show that the signal peptide of MMTV-Env precursor is also localized to this compartment (16,17). It turns out that this is not an isolated case, as it was recently shown that the leader sequence of HERV-K is also localized in the nucleolus (22).…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Although a variety of viral proteins are translocated into the nucleolus following viral infection (33), we were the first to show that the signal peptide of MMTV-Env precursor is also localized to this compartment (16,17). It turns out that this is not an isolated case, as it was recently shown that the leader sequence of HERV-K is also localized in the nucleolus (22).…”
Section: Discussionmentioning
confidence: 75%
“…1A). These were double-stained for p14 and B23, a nucleolar shuttling protein that also binds p14 (17,18). As can be seen in Fig.…”
Section: Intracellular Localization Of Mutant P14smentioning
confidence: 99%
See 3 more Smart Citations